AB0087 Higher levels of th17/23, TH2 and proinflammatory cytokines levels in synovial fluid of rheumatoid arthritis compared with psoriatic arthritis. (23rd January 2014) - Cañete, J.D.; Celis, R.; Ramirez, J.; Fernández-Sueiro, J.L.; Ruiz-Esquide, V.; Hernández, M.V.; Sanmartí, R.
Abstract : Background: Rheumatoid arthritis (RA) and Psoriatic arthritis (PsA) are two chronic inflamatory diseases mediated by the immune system with joints as main targets. Both diseases seem to exhibit a Th1/Th17 pattern, but studies including joint cytokines and clinical variables are scarse and inconclusive. Objectives: To compare concentrations of Th1, Th2, Th17/23 and other proinflammatory cytokines in Synovial fluid, as well as their relation with disease activity, between RA and PsA patients. Methods: Synovial fluid was obtained from a inflammed knee joint of RA and PsA patients. SF concentrations of Th1, Th2, Th17 and proinflammatory cytokines were determined by Quantibody® Human Th17 Array (RayBiotech, GA, USA). Clinical and biological data were collected at inclusion. Results: 82 RA and 48 PsA patients were included. 78% and 21% of them were women; mean age was 57 and 47.6 years; disease duration 10.2 and 9.3 years; DAS28 4.94 and 3.80 (p<0.001), respectively. No significant differences were found in systemic (CRP and ESR) and synovial (SF IL-6 levels and ST CD68+ macrophages/mm 2 ) between both groups. IL-17F, IL-21, IL-22 and IL-23 SF levels were significantly higher (p<0.001, p=0.01, p=0.02 and p<0.001, respectively) in RA patients compared with PsA patients. Also SF levels of IL-12p70, IL-10, TGFb1, IL-1 beta, TNFalpha, TNF-beta and CCL20 were significantly higher (p=0.03, p<0.001, p<0.001, p<0.001, p=0.04 and p<0.001, respectively) in RA than in PsA patients. In RA, DAS28 correlated with IL-21 (p=0.008) and CCL20 (p=0.001) levels; CRP with IL-10 (p=0.043) and CCL-20 (p<0.001); ESR with IL-10 (p=0.006), IL-17 (p=0.006) and CCL20 (p<0.001); TJC and SJC correlated with IL-21 (p=0.041 and p=0.028) and CCL20 (p=0.021 and p=0.02); RF levels was correlated with IL-2 (p=0.034), IL-4 (p=0.044), IL-10 (p=0.048) and CCL20 (p=0.019), and CCP levels with IL-4 (p=0.025) and CCL20 (p=0.026). In PsA, SF IL-17 levels correlated with SJC (p=0.026) and CRP levels (p=0.001), and IL-10 and CCL 20 levels with erosive disease (p=0.020 and p=0.006, respectively). Conclusions: SF Th17/23, CCL20 (a chemoskine attracting CCR6+ Th17 cells), Th2, and proinflammatory cytokines levels are all higher in RA patients compared with PsA patients matched by systemic and Synovial inflammation. IL-21 and CCL20 levels correlated with disease activity in RA, while in PsA IL-17 levels correlated with markers of systemic inflammation. Disclosure of Interest: None Declared